2001
DOI: 10.1080/15230430.2001.12003425
|View full text |Cite
|
Sign up to set email alerts
|

East Antarctic Climate and Environmental Variability over the Last 9400 Years Inferred from Marine Sediments of the Bunger Oasis

Abstract: Sediment cores around Antarctica provide a unique opportunity to cross check and supplement the climatic information recorded in ice cores. Suitable highresolution data, however, have not been available until now from East Antarctica. We present results from the longest continuous postglacial marine sediment succession (1290 cm) ever obtained from an East Antarctic basin. Twenty-one radiocarbon dates show a consistent age to depth correlation over the last 9400 calibrated years BP (cal. yr BP). For this time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…yr BP more open-water taxa are found in the Pup Lagoon core, suggesting warmer conditions. Similarly, a climate optimum is recognised in the Bunger Hills between 3500 and 2500 yr BP (Kulbe et al, 2001), in the Vestfold Hills around 4000 14 C yr BP (Roberts and McMinn, 1998) and in the Windmill Islands between 4000 and 1000 yr BP (Cremer et al, 2001(Cremer et al, , 2003a, suggesting this warm period (mid-Holocene Hypsithermal) may be a general trend in terrestrial Antarctica as reviewed by Hodgson et al (in press) and Ingó lfsson et al (1998). This period of a general warmer climate in Antarctica is detected in several proxy-climate records of Antarctica Hodgson et al, 2003) and is being considered as a potential analogue for the study of some aspects of the recent temperature rise in the Antarctic peninsula (Vaughan et al, 2003) that lead to the break up of large ice shelves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…yr BP more open-water taxa are found in the Pup Lagoon core, suggesting warmer conditions. Similarly, a climate optimum is recognised in the Bunger Hills between 3500 and 2500 yr BP (Kulbe et al, 2001), in the Vestfold Hills around 4000 14 C yr BP (Roberts and McMinn, 1998) and in the Windmill Islands between 4000 and 1000 yr BP (Cremer et al, 2001(Cremer et al, , 2003a, suggesting this warm period (mid-Holocene Hypsithermal) may be a general trend in terrestrial Antarctica as reviewed by Hodgson et al (in press) and Ingó lfsson et al (1998). This period of a general warmer climate in Antarctica is detected in several proxy-climate records of Antarctica Hodgson et al, 2003) and is being considered as a potential analogue for the study of some aspects of the recent temperature rise in the Antarctic peninsula (Vaughan et al, 2003) that lead to the break up of large ice shelves (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The drop in TOC and δ 13 C in core PG1173 at 2.2 ka bp was previously interpreted as an abrupt cooling (Kulbe et al 2001). However, this shift clearly predates a late Holocene increase in sea ice diatoms at 1.7 ± 0.1 ka bp (Fig.…”
Section: Environmental Historymentioning
confidence: 67%
“…Datasets include lithological descriptions (changes in sediment colour, fabric, grain size and organic remains), total organic carbon (TOC), total nitrogen (N) and total sulfur (S) contents, stable carbon isotope ratios of TOC (δ 13 C) and mineralogical composition. For two cores (PG1173, PG1180) diatom assemblage data was presented in Kulbe et al (2001) and Verkulich et al . (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that there was a short return to stratified, open-water conditions and a reduction in near-shore winter sea-ice extent. A climate optimum in the Bunger Hills between 3500 and 2500 BP was inferred by Kulbe et al (2001). Roberts et al (2004), based on the lake sediment record from Windmill Islands, East Antarctica, suggested that from c. 2800 BP the retreat of the ice margin led to increasing meltwater inputs and freshening of the lake basin until c. 1900 BP.…”
Section: Strontium Isotopementioning
confidence: 99%